PENGEMBANGAN LKS BIOLOGI SMA BERBASIS PRAKTIKUM DENGAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA - Mirawati, Baiq; Royani, Ida (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2019)
[Title: Development of Student Worksheets based on Practicum with Direct Learning Models to Improve Students' Science Process Skills]. This research aims to develop student worksheets based on practicum with direct learning models that valid, practical and effective to improve students' science process skills. This research is a development study using 4D stages with the subject of 30 students of class X1 IPA1 MAPK Syeh Zainuddin Anjani. The developed student worksheet was validated by three competent validators using validation sheets. The practicalities of the worksheets developed were measured using student response questionnaires, while the effectiveness of worksheets was measured using an observation sheet of students' science process skills by two observers. Research data were analyzed descriptively and quantitatively. The results showed that the student worksheets with tissue culture material were quite valid (a score of 3.9), the students' responses after learning showed a high percentage with a very strong category (81%-100%), while the students' process skills improved at each meeting in the good category. Based on the results of the study, it can be concluded that the student worksheets based on practicum with direct learning models were valid, practical, and effective to improve the students science process skills of MAPK Syeh Zainuddin Anjani.